Effect of hypoxic training on angiogenetic regulators and mesenchymal stem cells - de Marees, M.; Wahl, P.; Suhr, F.; Achtzehn, S.; Schmidt, A.; Bloch, W.; Mester, J. (Science and Skiing IV, 2008)
INTRODUCTION: Physical activity is a strong Stimulus for the body which can induce tissue damage and tissue remodelling. Both processes are strongly connected with the activity of stem and progenitor cells. It was shown the endothelial progenitor cells (EPC) may have impact on endothelial tissue repair. Mesenchymal stem cells (MSC) can support the repair of muscle, bone, and cartilage tissues. Recent studies showed the influence of physical activity on EPC [1J and MSC [2]. As altitude is an often chosen Stimulus in various sports, such as CC-skiing, swimming and rowing the aim of our study was to analyze the effect of a conventional altitude training camp (LH-TH) on the migratory activity of MSC.